Effects of heater orientation on critical heat flux for nanoparticle deposited surface with honeycomb porous plate attachment in saturated pool boiling of water - Mt Aznam, Suazlan; Mori, Shoji; Sakakibara, Fumiki; Okuyama, Kunito (Elsevier Ltd, 2016)
One of the main concerns regarding in-vessel retention (IVR) during a severe accident is guaranteeing sufficient cooling performance to avoid the melt-through of the pressure vessel. In such an event, the vessel is submerged in water, and boiling is occurred to remove the heat. However, the main problem is that there is a limit to the pool boiling heat transfer at the outer surface of the reactor vessel due to the occurrence of critical heat flux (CHF) conditions. Therefore, to enhance the capability of IVR in light-water reactors during states of emergency, methods of increasing the CHF should be considered. In our previous study, it was demonstrated that the pool boiling CHF can be increased approximately twofold by simply attaching a honeycomb porous plate to an upward-facing plain heated surface under saturated and atmospheric conditions. On the other hand, it is well known that the CHF for a heated surface is greatly enhanced by nanoparticle deposition because of the resulting improvement in surface wettability. In IVR, it is important to determine the CHF for downward-facing heated surfaces. Therefore, the objective of this paper is to examine the effect of the heater orientation on the CHF in combination with surface modification by honeycomb porous plate attachment and nanoparticle deposition. A pool boiling CHF experiment of water is performed under saturated temperature and atmospheric pressure conditions. Compared with a plain surface, the CHF is shown to be greatly increased by a combination of the honeycomb porous plate attachment and nanoparticle deposition, even under downward-facing heater conditions. Additionally, the CHF enhancement increases as the orientation of the heated surface approach downward-facing.